2018
DOI: 10.3390/v10110623
|View full text |Cite
|
Sign up to set email alerts
|

Following in the Footsteps of the Chikungunya Virus in Brazil: The First Autochthonous Cases in Amapá in 2014 and Its Emergence in Rio de Janeiro during 2016

Abstract: Currently, Brazil lives a triple arboviruses epidemic (DENV, ZIKV and CHIKV) making the differential diagnosis difficult for health professionals. Here, we aimed to investigate chikungunya cases and the possible occurrence of co-infections during the epidemic in Amapá (AP) that started in 2014 when the first autochthonous cases were reported and in Rio de Janeiro (RJ) in 2016. We further performed molecular characterization and genotyping of representative strains. In AP, 51.4% of the suspected cases were conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 67 publications
1
19
0
Order By: Relevance
“…Despite its synchronicity, there is still limited information about the genomic epidemiology of CHIKV during the Brazilian epidemics. To provide more information about the dynamics of CHIKV epidemics in Brazil, we generated 23 new near-complete genome sequences from Rio de Janeiro that had the first detection of CHIKV in 2016 and experienced an explosive outbreak in 2019 [10,[12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its synchronicity, there is still limited information about the genomic epidemiology of CHIKV during the Brazilian epidemics. To provide more information about the dynamics of CHIKV epidemics in Brazil, we generated 23 new near-complete genome sequences from Rio de Janeiro that had the first detection of CHIKV in 2016 and experienced an explosive outbreak in 2019 [10,[12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…A year later, in 2014, in Brazil, the co-circulation of the Asian and ECSA genotypes were reported in Northern and Northeastern, respectively [8,9]. Since then, the ECSA genotype has been detected in several other Brazilian states in the northeastern, southeastern, and northern regions, exerting a serious threat to public health [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The application of Bayesian statistical inference framework, can allow the reconstruction of the geographic history of the still ongoing and never reported before epidemic on the basis of the first isolates sampled at known times . It has been showed that CHIKV was imported to the Americas from South‐East Asia …”
Section: Phylogenesis and Phylodynamic Of Arbovirusesmentioning
confidence: 99%
“…180 It has been showed that CHIKV was imported to the Americas from South-East Asia. [181][182][183][184][185] During CHIKV outbreak in 2005 and 2006, nonsynonymous mutation (A226V) occurred both on La Reunion and in some Indian CICCOZZI ET AL.…”
Section: The Phylogeny Of Genotypes B and Cmentioning
confidence: 99%
“…The first chikungunya virus (CHIKV) epidemic in Rio de Janeiro city, the second most populated city in Brazil and its main tourist destination, occurred in 2016 (de Souza et al, 2018).…”
Section: Introductionmentioning
confidence: 99%